Maria Montessori`s pedagogy in the Lublin region. Thirty years of educational activities and perspectives of development - Beata Bednarczuk (Studia z Teorii Wychowania, 2023)
The aim of the paper is presentation of the history of thirty-year activities including dissemination of Maria Montessori's alternative system of education in the Lublin region. In the 1992 – 1994 years the project of Individualized Education based on the Montessori method assumptions became realized in the Institute of Pedagogy of the Maria Curie-Skłodowska University in Lublin. This resulted in development of an alternative way of thinking about education, creating mixed grade classrooms whose work is based on the Montessori approach as well as initiating a new trend in the educational and research activities in the Institute of Pedagogy, Maria Curie-Skłodowska University in Lublin. But first of all educational activities proved to be essential for the children`s developmental achievements and popularization of the ideas of Montessori pedagogy in Poland. The paper presents multi-concept activities and their documentary evidence in the synthetic way. The development perspectives and challenges for the Montessorian educators in the region are outlined.